Prototipe Sistem Parkir Otomatis Berdasarkan Topologi Kampus Syahdan, Universitas Bina Nusantara - Liawatimena, Suryadiputra (CommIT (Communication and Information Technology) Journal, 2008)
Article clarified a source of learning and research on the design of Automatic Parking System. That was implementedat Syahdan Campus, Bina Nusantara University. The research methods done were library. Literature study was done bystudying and looking for articles about matters related and laboratory research method the development of existing parkinglots. Meanwhile, the laboratory study was done by creating algorithm designs will be used to detect the parking lot, designingof physical design, and simulation system which will be created. This system used sensors to detect whether there were the carsor not. Then it will be sent via RS-485 for the farthest distance. The results of sensor reading will be displayed on PC. It canbe concluded that by using this system, the park users will be more efficient and flexible in the service.Keywords: automatic parking system, sensor, RS-485, campus topology